2022
DOI: 10.1371/journal.pone.0270987
|View full text |Cite
|
Sign up to set email alerts
|

Small-scale field assessment against the dengue vector Aedes aegypti using the auto-dissemination approach in an urban area of Vientiane, Lao PDR

Abstract: Background In Lao PDR, dengue fever is the most important vector borne disease and vector control remains the principal method to fight against Aedes aegypti the primary transmitter mosquito species. Vector control management programs need new strategies in addition to conventional larviciding and adulticiding interventions in the country. In this study, we examined the In2Care® Mosquito Trap’s efficacy using insecticide auto-dissemination strategy. The insecticide pyriproxyfen, present in powder form inside t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…One of the most effective ways to reduce dengue cases is to manage the vector that carries the DENV. The use of AD-PPF as a strategy to control mosquito density has been proven effective based on previous research [ 46 , 47 , 48 ]. In the Philippines, previous research has tackled the use of AD-PPF in a small urban community in Metro Manila using a small sample size; the results of this study showed that dengue seroconversion rates decreased in the treated population, but not significantly so.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most effective ways to reduce dengue cases is to manage the vector that carries the DENV. The use of AD-PPF as a strategy to control mosquito density has been proven effective based on previous research [ 46 , 47 , 48 ]. In the Philippines, previous research has tackled the use of AD-PPF in a small urban community in Metro Manila using a small sample size; the results of this study showed that dengue seroconversion rates decreased in the treated population, but not significantly so.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most effective ways to reduce dengue cases is to manage the vector that carries the DENV. The use of AD-PPF as a strategy to control mosquito density has been proven effective based on previous research [39][40][41]. In the Philippines, previous research tackled the use of AD-PPF in a small urban community in Metro Manila using a small sample size in which results showed that dengue seroconversion rates decreased in the treated population but not significantly so.…”
Section: Discussionmentioning
confidence: 99%
“…The first is autodissemination augmented by males (ADAM), which utilizes laboratory- or factory-reared male mosquitoes that are treated with an insect growth regulator (IGR) and released into the natural environment, where they can directly deliver an IGR to cryptic larval habitats or indirectly by copulating with naturally occurring females ( 14 , 15 ). The second is autodissemination stations, which rely on attracting females to a station wherein they are then exposed to non-lethal doses of an IGR and leave the station to disseminate the IGR to cryptic larval habitats ( 5 , 7 , 10 , 11 , 13 , 16 18 ).…”
Section: Introductionmentioning
confidence: 99%